Rancang Bangun Hand Sanitizer Otomatis Berbasis Mikrokontroler - Iwan Purnama; Rizki Hariandi; Nurhayati; Fauzan Azim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Hand washing is very important to keep hands and skin clean. Hand washing can be done by washing hands with soap and clean running water. To prevent the spread of the corona virus, the government urges the public to comply and be disciplined in implementing health protocols, one of which is by always washing hands using a hand sanitizer. The majority of hand sanitizers use conventional hand sanitizers, namely by directly touching the hand sanitizer bottle. The purpose of this research is to make an Arduino-based automatic hand sanitizer. This automatic hand sanitizer tool uses an Arduino Uno as a system controller, an ultrasonic sensor as a hand movement detector and a micro servo as an actuator to press the hand sanitizer bottle lever. This research produces an automatic hand sanitizer tool that can be used without having to touch the hand sanitizer bottle directly, thereby reducing the risk of transmission of Covid-19 when washing hands